2009
DOI: 10.1246/cl.2009.880
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Concentration Dependence of Photoinduced Charge Separation Reaction between Zinc Tetraphenylporphyrin and Duroquinone Studied by Laser Flash Photolysis

Abstract: Ethanol concentration dependence of photoinduced charge separation between zinc tetraphenylporphyrin (ZnTPP) and duroquinone (DQ) in benzonitrile was studied by nanosecond laser flash photolysis. Acceleration of the photoinduced charge separation reaction rate by hydrogen bonding between DQ anion radical and ethanol was observed. A simple analysis in the framework of the Marcus theory indicated that the observed electron-transfer reaction rate was affected not only by the decrease of the reaction free energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The parameters affected by the addition of alcohols are Δ G and λ. In the previous study, we demonstrated that the alcohol concentration dependence of k CS was not explained by the change of Δ G alone . We have proposed the increase in λ with the addition of alcohol in the present photoinduced CS reaction system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The parameters affected by the addition of alcohols are Δ G and λ. In the previous study, we demonstrated that the alcohol concentration dependence of k CS was not explained by the change of Δ G alone . We have proposed the increase in λ with the addition of alcohol in the present photoinduced CS reaction system.…”
Section: Discussionmentioning
confidence: 87%
“…For the EtOH concentration dependence of k CS , the reported chemical equilibrium constants ( K ≈ 0 (mol dm −3 ) −1.3 and K − = 85 (mol dm −3 ) −1.3 ) are used. The constant parameters used are Z = 5 × 10 11 mol −1 dm 3 s −1 , λ° = 0.9 eV, and −0.05 eV for Δ G in the absence of alcohols. The CS process in the present ET system is in the Marcus normal region (λ > −Δ G ).…”
Section: Discussionmentioning
confidence: 98%
“…Prior experimental studies on electron transfer in hydrogen-bonded systems have come to the conclusion that hydrogen-bond formation and breakage can contribute substantially to the reorganization energy (λ) accompanying the electron-transfer event. Therefore we explored the temperature dependence of τ CR in order to obtain information about the activation energies ( E A ) for thermal charge recombination. Figure shows Arrhenius plots based on lifetime measurements in CH 3 CN between 5 and 70 °C (Supporting Information Figure S3 for TAA-Ru II -AQ and Figure S4 for TAA-Os II -AQ) and in HFIP between 5 and 50 °C (Supporting Information Figure S5 for TAA-Ru II -AQ and Figure S6 for TAA-Os II -AQ).…”
Section: Resultsmentioning
confidence: 99%